IKN Nusantara: Driver of Sustainable Economic Growth for Indonesia's Future - Eka Hendi Andriansyah; Waspodo Tjipto Subroto; Norida Candra Sakti; Irwan Adimas Ganda Saputra (International Forum of Researchers and Lecturers, 2025)
This study explores the relocation of Indonesia's capital from Jakarta to Nusantara (IKN), a strategic initiative aimed at addressing environmental, economic, and social challenges while fostering sustainable economic growth. Utilizing a Systematic Literature Review (SLR) methodology, the research examines existing studies to assess the potential and challenges associated with the project. Key findings highlight IKN's role in redistributing economic activities, mitigating Jakarta's overpopulation and infrastructure strain, and promoting regional development in East Kalimantan. The project is expected to enhance national GDP distribution, create millions of jobs, and position IKN as a smart and sustainable urban model. However, concerns over financing, environmental impacts, and socio-cultural adaptations present critical challenges that require comprehensive strategic planning. This study contributes to the discourse on national capital relocation, providing insights for policymakers to optimize the economic and environmental benefits of this transformative endeavor.